2010
DOI: 10.3390/molecules15085797
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Constituents of Essential Oil from Cones of Pinaceae spp. Natively Grown in Turkey

Abstract: In this study, the yields and composition of essential oils obtained from the cones of Pinaceae family species natively grown in Turkey were investigated. Essential oils were obtained by hydrodistillation. Oil yields were 0.13-0.48 mL/100 g in pine cones, 0.42-0.59 mL/100g in fir, 0.36 mL/100g in spruce and 0.37 mL/100g in cedar. While α-pinene (47.1-14.8%) was the main constituent of P. slyvestris, P. nigra and P. halepensis, limonene (62.8%) in P. pinea and β-pinene (39.6%) in P. brutia were found in higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
67
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 19 publications
10
67
2
2
Order By: Relevance
“…The observed yields were comparable to those reported in the literature (Tazerouti et al, 1993;Roussis et al, 1995;Hmamouchi et al, 2001;Macchioni et al, 2003;Dob et al, 2007;Tumen et al, 2010;Abi-Ayad et al, 2011;Ustun et al, 2012).…”
Section: Essential Oils Yieldssupporting
confidence: 94%
See 2 more Smart Citations
“…The observed yields were comparable to those reported in the literature (Tazerouti et al, 1993;Roussis et al, 1995;Hmamouchi et al, 2001;Macchioni et al, 2003;Dob et al, 2007;Tumen et al, 2010;Abi-Ayad et al, 2011;Ustun et al, 2012).…”
Section: Essential Oils Yieldssupporting
confidence: 94%
“…Our results showed the presence of caryophyllene oxide (0-12.5%) as a major component, which was also the major component at 48.2% and 0.4-7.8% in the essential oils from Ghazaouet (T 1 ) and Turkey, respectively, but, it was absent in the case of Greece, Italy, Morocco, Turkey and the rest areas from Algeria. Furthermore, the humulene oxide and thumbergol were present in the essential oils from Ghazaouet (T 1 ) at 6.7% and 8.3%, respectively, while, they were absent in our results and those of the previous studies (Tazerouti et al, 1993;Roussis et al, 1995;Hmamouchi et al, 2001;Macchioni et al, 2003;Dob et al, 2007;Tumen et al, 2010;Abi-Ayad et al, 2011;Ustun et al, 2012). This chemical variability among provenances led to conclude that geographic variation may influence the essential oils components either in quantitative and qualitative extent.…”
Section: Essential Oil Compositioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Also, this variability could affect the yield of extraction of the essential oil. In our study, the results of extraction showed that the yield of hydrodistilation was 0.18 , which is in agreement with the study of Tumen et al 55 who showed that the yield of the essential oil of P. halepensis grown in Turkey was 0. 20 .…”
Section: Discussionsupporting
confidence: 82%
“…This family is a taxonomic group of high economic importance in the production of paper, timber, construction materials, chemicals, and essential oils used for perfume or pharmaceutical and aromatherapy purposes (Salem et al 2015b). Previous studies have been dedicated to analyzing the chemical composition of the essential oils and the antimicrobial activities of several parts of Pinaceae members (needles, branches, cones, seeds, and bark) (Grassmann et al 2003;Nikolić et al 2007;Tumen et al 2010;Bier et al 2016;Fattahi et al 2016;Salem et al 2016). Nevertheless, the majority of studies regarding the chemical composition of softwood species have related to North American and Central European species (Hennig et al 1994;Danneyrolles et al 2016;Greenberg et al 2016;Krieg et al 2016).…”
Section: Introductionmentioning
confidence: 99%